Survival Outcomes in the Patients of Ovarian Epithelial Carcinomas Treated with Fertility-Sparing Surgery: A Study from a Developing Country - Azhar, Musa; Khan, Shafquat Ali; Hamdani, Syed Abdul Manan; Yasmeen, Tahira; Yasmeen, Samia; Awan, Umme-e-Kalsoom; Syed, Aamir Ali; Siddiqui, Neelam (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the outcomes of fertility-sparing surgery in patients with ovarian epithelial carcinoma treated at our centre.Study Design: Retrospective longitudinal study.Place and Duration of Study: Shaukat Khanum Memorial Cancer Hospital & Research Center, Lahore Pakistan, from Jul 2001 to Aug 2015.Methodology: We studied 31 patients with ovarian epithelial carcinoma who underwent fertility-sparing surgery at Shaukat Khanum Memorial Hospital. The detail regarding patients and tumour characteristics, along with outcomes of the intervention, was obtained from secondary data kept in the electronic hospital information system.Results: A total of 132 patients with ovarian epithelial carcinoma were identified; 31 patients underwent fertility-sparing surgery (Stage-IA, n=19; Stage-IC, n=12). By histopathology, 14(45.0%) had mucinous cystadenocarcinoma, 7(22.6%) serous adenocarcinoma, 6(19.4%) endometroid, and 4(12.9%) with clear cell pathology. The mean duration of follow-up was 52.6±2.3 months (18-118 months) after fertility-sparing surgery. Five-year recurrence-free survival was 81.0%. (Three-year=89.0%), using the Kaplan-Meier graph. Three patients had successful pregnancies, with one having a twin pregnancy.Conclusion: Fertility-sparing surgery should be considered for children of early-stage epithelial ovarian carcinoma patients as it preserves fertility and endocrine function while avoiding recurrence.